Bio-inspiration from the Issus Nymph gear − strength analysis - Guilbert Bérengère; Winger Marie; Cavoret Jérôme; Sutton Gregory; Johnston Richard; Ville Fabrice (Mechanics & Industry)
Planthoppers are champion jumpers. Adult specimens are propelled by rapid movements of the hind legs, which can launch them a horizontal distance of 1.1 m with a take-off speed of 5.5 m/s, demonstrating high power output. The planthopper Issus Coleoptratus nymph achieves the precise synchronization required (30 μs) thanks to a pair of cuticular gears that kinematically link the hind legs. These cuticular gears show spectacular geometrical differences from conventional man-made mechanisms. We analysed the gear teeth of Issus Coleoptratus in combination with Micro-CT scans of the teeth to study the gearing properties. The results show that the Issus gear has a higher contact ratio than conventional man-made involute spur gears. If the Issus gear is rescaled to a tooth size equivalent to a conventional gear module of 4.5mm, an ISO standard involute gear can mesh, with no problem, with the Issus gears. In simulations, if the resized gear is subjected to the load borne by a conventional automotive gear made of steel, the maximum stress obtained for the Issus gear is higher on the tooth flank than for the conventional gear. This is a potentially interesting result, as one of the disadvantages of the ISO gear is that failure generally occurs at the root of the tooth due to stress concentration, leading to gear failure. Finally, a strength analysis is carried out with the application of the real load transmitted by the gear during a badly engaged jump showing that, thanks to its gear high contact ratio, it is possible for the Issus to compensate for any problems arising from a non-symmetrical jump, and therefore to perform a synchronized jump in any poorly engaged situation.